THE IMPLEMENTATION OF JUMBLED-SENTENCES TOWARD STUDENTS’ SKILL IN WRITING REPORT TEXT - Fatmawati Setia Utami; Mustaqim Pabbajah; Juhansar Juhansar (University of Kuningan, 2018)
This study aims at describing the implementation and the effectiveness of jumbled-sentences as a technique to enhance students’ skill in writing report text and finding out the factors influencing students’ skill in writing report text. This study was conducted in MAN 2 Yogyakarta that involved 24 tenth graders of IPA 3 in academic year 2018/2019. This study was a classroom action research. To collect the data, observation checklist, structured interview, and tests were used. The result showed that most of students could understand the subject easily and involve actively during the technique implementation. Besides, the test results showed students’ mean improvement in writing report text from pre-test (3.00), post-test I (3.36), and post-test II (3.78). It means that jumbled-sentences technique is effective to enhance students’ skill in writing report text. Moreover, the factors influencing students’ writing skill were having lack of vocabulary, getting anxiety in making grammar errors, getting difficulties in understanding and translating words or sentences, and having limited classroom for learning-teaching process.Keywords: implementation, jumbled-sentences, students’ skill, writing, report text.